Digitalization of Differentiated History Teaching Materials Based on Galuh Regents History to Improve Students’ Critical Thinking Ability - Fachrurozi, Miftahul Habib; Sofiani, Yulia; Armiyati, Laely (Universitas Negeri Padang, 2025)
This research aims to develop differentiated digital history teaching materials based on Galuh regents' history to enhance students’ critical thinking. These teaching materials integrated differentiated learning concepts, including content differentiation, learning style accommodations (visual, auditory, kinesthetic), and products differentiated on students’ task projects. This research employs the RnD method and is conducted through the ADDIE model. The subject of the study is a 10th-grade student enrolled in one of the Senior High Schools in Ciamis. Data collection involves interviews, questionnaires, observations, and tests. Data analysis is conducted qualitatively during the analysis and design stages and quantitatively during the development, implementation, and evaluation stages. The research findings are: 1) The current school teaching materials fail to meet students' needs. The teaching materials do not support highly digitised students' diverse learning styles and local historical content. 2) The development process involved expert judgment, receiving a score of 4.6 from the teaching material expert and 4.2 from the content expert. A limited trial yielded a score of 4.07, while an extensive trial yielded a score of 4.52. 3) Effectiveness testing showed an N-Gain of 0.7218 (72.18%), categorized as effective. Based on these findings, The history of Galuh regents holds significant character values in shaping students’ cognitive development so it can integrated into teaching materials. Future research should expand on digital local history learning by integrating interactive technology (AR/VR) to support student needs, particularly in digitalization and accommodating diverse learning styles.